PELAKSANAAN TEKNIK PERMAINAN DADU DALAM PEMBELAJARAN VOCABULARY - Lollo Rosa Lubis; Rika Sri Erdila; Lailatussiva Siregar; Ulfa Hakiki (Institut Pendidikan Tapanuli Selatan, 2022)
This research is motivated by the low ability to recognize children's words. The purpose of this study is to describe the improvement of children's abilitiesin saying the word through the game of dice.This type of research is classroom action research using quantitative approach. The subjects of this study were elementary school children on Jl.Sultan Hasanuddin 55. Data collection techniques used observation techniques, data collection tool using observation and data analysis in research it uses the percentage formula.The results of the study show that 1) the ability to recognize children's words in mentioning the word increases in the category of being able through the game dice. This can be seen from the average value for each statement increases with each meeting. This proves that through dice games can improve children's ability to mentioning words, 2) the ability to recognize children's words in connecting The word increases in the category able to go through dice game can be seen from the average value on each statement increases with each meeting. This proves that through dice games can improve word recognition skills child.